Psychic Therapy with Sholawat for Peace of Mind - Ulumiyah, Yusril Agus Tri; Istikomah, Istikomah (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
Practicing prayer with istikohmah can make the pattern of thinking and heart calm and make human morals better because praying makes a person remember Allah and His beloved Prophet SAW, which makes the human heart calm again. With a calm heart, this will be the cure for various diseases that are felt. This study aims to describe psychic therapy with prayer for peace of mind as a reference for healing psychological problems experienced by humans related to life problems. The result of this study is that respondents studied in this study after being given education related to sholawat have practiced it mystically and can change their personalities for the better and make their souls balanced. In addition, the practice of sholawat will provide nourishment and priority such as being granted and facilitating all his wishes, being the reason for the granting of prayers, being forgiven for his sins by Allah SWT, eliminating the sense of difficulty and hardship in his life. Sholawat is not only a prayer but also a means of psychotherapy against psychic disorders. This research has descriptive qualitative elements and researchively has an interactive descriptive nature that contains data from respondents. That way this research can be used as an educational means of psychotherapy on the problems of life experienced by humans to make the human soul calm and make humans more noble morals.